Postoperative exogenous endophthalmitis caused by Escherichia coli: a rare case report and literature review - Rami A Al-Dwairi; Abdelwahab Aleshawi; Zaki Shannak; Wafa Al-Shorman; Seren Al Beiruti; Ahmed Al Sharie (Future Science OA, 2023)
Aim: We report a rare case of postoperative endophthalmitis caused by Escherichia coli. Case description: The diagnosis of postoperative endophthalmitis in our patient was established based on the clinical signs of hypopyon along with vitritis. The patient underwent pars plana vitrectomy, anterior chamber washout, intraocular lens removal, and intravitreal antibiotics (amikacin and vancomycin) injection. The culture of both the vitreous sample and the intraocular lens, revealed a heavy growth of Escherichia coli. Conclusion: Escherichia coli is an unusual microorganism to cause postoperative endophthalmitis. A major breach in the sterilization may explain this infection. Proper sterilization and prophylactic measures are crucial to avoid this disastrous complication.